Removal of hydrogen sulfide from biogas using activated carbon synthesized from different locally available biomass wastes - a case study from Palestine. Issue 1 (1st January 2020) - Sawalha, Hassan; Maghalseh, Maher; Qutaina, Janna; Junaidi, Kholoud; Rene, Eldon R.
ABSTRACT: The main aim of this study was to remove hydrogen sulfide (H2 S) from biogas by adsorption using synthesized activated carbon prepared using locally available biomass. The effect of the type of precursors, impregnation reagent and bed height was studied in continuous reactors. Three types of biomass wastes (almond shells, eucalyptus and coffee grains) were collected, grinded, sieved, pyrolyzed at 500°C and impregnated with chemical reagents such as potassium hydroxide or zinc chloride. Adsorption tests were performed using a fixed bed filter filled with the produced activated carbon. The highest biochar yield of 36% was obtained eucalyptus followed by almond shells (28.5%) and coffee grains (24%), respectively. The highest adsorption capacity and removal efficiency were obtained with eucalyptus followed by almond shells and coffee grains, respectively. For instance, eucalyptus showed an adsorption capacity of 690 (mg hydrogen sulfide/g adsorbent) followed by almond (230 mg hydrogen sulfide/g adsorbent) and coffee grains (22 mg hydrogen sulfide/g adsorbent). As an impregnation reagent, potassium hydroxide gave the highest adsorption efficiency and capacity than zinc chloride. Furthermore, the breakthrough time with KOH (180 min) was higher than ZnCl2 (70 min). Increasing the bed height during continuous breakthrough tests increased the adsorption capacity and hydrogen sulfide removal efficiency. The results of this study showed that the adsorption efficiency of the synthesized activated carbon and consequently the hydrogen sulfide removal efficiency could be fine-tuned by selecting an appropriate biomass precursor and proper impregnation reagent. Graphical abstract: